The Importance of Digital Marketing As an MSME Marketing Strategy: A Literature Review - Sudarsono Sudarsono; Rinto Yusuf (West Science Journal Economic and Entrepreneurship, 2023)
Small, medium and micro enterprises (MSMEs) play an important role in driving the economy of the community, especially in certain regions. This is indicated by the fact that most of the population works in this industry. However, in reality, small and medium enterprises (MSMEs) often use traditional methods to sell their goods, namely selling directly to consumers. Observations show that they face challenges in adopting today's rapidly evolving information technology, resulting in a limited market. The study used Mendeley, Google Scholar, and Semantic Scholar to conduct a literature review. From this exposition, it can be concluded that MSMEs must utilize the latest technology to increase revenue to expand market share. In order for them to compete in a wider market, they must also make their products stand out because they are unique.